Development of ic-ELISA and an immunochromatographic strip assay for the detection of methylmercury. Issue 4 (4th July 2017) - Zou, Shuzhen; Cui, Gang; Liu, Liqiang; Song, Shanshan; Kuang, Hua
ABSTRACT: In this study, we developed an indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) and an immunochromatographic strip assay based on a monoclonal antibody (mAb) against methylmercury (MeHg) to detect the presence of MeHg in tap water. Under optimum conditions (pH 8.0, 0.8% NaCl, and 0.1% Tween 20), the 50% half maximal inhibitory concentration (IC50 ) and limit of detection (LOD) were 16.64 and 2.03 ng/mL, respectively. The anti-MeHg mAb was speciﬁc to mercury with no cross-reactivity with other metal ions. The cut-off value of the immunochromatographic strip assay was 500 ng/mL for semi-quantitative detection, and the LOD was 11.3 ng/mL for quantitative detection. The average recovery rates of the ic-ELISA and immunochromatographic strip assay were 98.13% and 107.87%, respectively, in tap water. Therefore, ic-ELISA and the immunochromatographic strip assay can be used to detect MeHg in tap water.